ADDRESSING GENETIC DISCRIMINATION IN THE MEDICAL TAKAFUL SYSTEM IN MALAYSIA - Saifuddeen, Shaikh Mohd; Mohamad, Muhammad Hisyam (Online Journal of Research in Islamic Studies, 2017)
The progress achieved by man in the field of medicine and biotechnology thus far is indeed commendable as it has paved the way to a better quality of life. For instance, the advancement in genetic technology has made early detection of genetic disorder possible. Similarly, the development in gene therapy techniques has raised chance in alleviating and curing genetically-linked diseases which the hope in treatment of such diseases was slim in the past. Nonetheless, in spite of beneficial effects the progress in this field may bring to us especially in regard to human health, they may not be seen as good from another angle. One of the adverse effects of the proliferation of genetic technology is the potential misuse of genetic information by health insurance companies. Thus, this article seeks to analyse the issue of genetic screening and its potential impacts on the medical takaful system (Islamic medical insurance) in Malaysia. The article will also try to explain that in the absence of acceptable solutions for certain predicaments within the existing frameworks, Islam offers its own approach that is practical and ultimately leads toward inculcating universal values such as cooperation and brotherhood in members of society.